Prevalence of periodontitis and systemic inflammation assessed by C reactive protein in Sudanese hemodialysis patients with end stage renal disease - Mohammed, Sara Hamid; Hashim, Nada Tawfig; Adam Abduljalil, Salma Musa; Homyda, Randa Mohamed Ali; Rahman , Muhammed Mustahsen; Gismalla, Bakri Gobara (Acta Biomedica Atenei Parmensis, 2026)
Background: A potential bidirectional link between periodontitis and systemic diseases, including end-stage renal disease (ESRD), has long been speculated. Elevated systemic inflammation in ESRD patients may be exacerbated by chronic periodontal infection. This study aimed to assess the prevalence of periodontitis and its association with systemic inflammation, measured by serum C-reactive protein (CRP), in Sudanese patients receiving hemodialysis. Methods: A multicenter, hospital-based, analytic cross-sectional study was conducted at six dialysis centers in Khartoum. One hundred ESRD patients aged 25–45 years, on maintenance hemodialysis, were recruited. Periodontal examination included plaque index (PI), bleeding on probing (BOP) , probing pocket depth (PPD), and clinical attachment loss (CAL). Serum CRP levels were measured using immunofluorescent assay (cutoff >10 mg/L). Results: The prevalence of periodontitis was 83%, with moderate cases being most common (47%). Mean CRP level in periodontitis patients was 7.89 ± 7.92 mg/L. No statistically significant association was found between periodontitis and elevated CRP (P = 0.99), nor between CRP and periodontal parameters (PI, BOP, PPD, CAL). However, CAL was significantly associated with gender (P = 0.036), and it showed a marginal association with dialysis duration (P = 0.242). Conclusion: Periodontitis is highly prevalent among ESRD patients on hemodialysis in Sudan, yet it was not found to be associated with elevated systemic inflammation as measured by CRP. Further studies with larger sample sizes and additional biomarkers are warranted to explore this relationship more deeply.